1996
DOI: 10.1046/j.1365-2141.1996.d01-1744.x
|View full text |Cite
|
Sign up to set email alerts
|

Tucaresol increases oxygen affinity and reduces haemolysis in subjects with sickle cell anaemia

Abstract: The primary pathophysiological event in sickling is the intracellular polymerization of deoxygenated haemoglobin S. Tucaresol (589C80;4[2-formyl-3-hydroxyphenoxymethyl] benzoic acid), a substituted benzaldehyde, was designed to interact with haemoglobin to increase oxygen affinity and has been shown to inhibit sickling in vitro. We administered tucaresol to sickle cell patients in the steady state to examine the anti-sickling effect in vivo. Oral doses of tucaresol or placebo were given to nine stable sickle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 14 publications
3
52
0
Order By: Relevance
“…Tucaresol has proved effective against experimental models of cytomegalovirus and murine colon adenocarcinoma and has been shown to be biologically active as an immunopotentiator, favoring a Th1 response in patients with malignant melanoma (29,36). Tucaresol was well tolerated at doses of 400 mg/kg of body weight in phase I and II melanoma trials (29), and an elimination half-life of 1 week was shown in other studies (4). The costimulatory potential of tucaresol, as well as its ability to bias immunity toward a cellmediated T-helper-cell response, suggests that it could prove to be of therapeutic benefit against chronic infectious diseases such as VL, which is characterized by its ability to induce T-cell anergy (26).…”
mentioning
confidence: 99%
“…Tucaresol has proved effective against experimental models of cytomegalovirus and murine colon adenocarcinoma and has been shown to be biologically active as an immunopotentiator, favoring a Th1 response in patients with malignant melanoma (29,36). Tucaresol was well tolerated at doses of 400 mg/kg of body weight in phase I and II melanoma trials (29), and an elimination half-life of 1 week was shown in other studies (4). The costimulatory potential of tucaresol, as well as its ability to bias immunity toward a cellmediated T-helper-cell response, suggests that it could prove to be of therapeutic benefit against chronic infectious diseases such as VL, which is characterized by its ability to induce T-cell anergy (26).…”
mentioning
confidence: 99%
“…The scientific rationale for this biomarker was based on the observation that HbS polymerization is inhibited when 20-30% of hemoglobin is maintained in the oxy-conformation. Measurements of %MOD were included in the initial phase I studies and used to guide dose tucaresol dosage in the initial patient studies (55,56).…”
Section: Biomarkers In Early (Exploratory) Phase Clinical Developmentmentioning
confidence: 99%
“…We were also able to make accurate predictions about the likely clinical dose based on the use of this required to test this hypothesis. During the time while surrogate, as in sickle cell disease patients, %MOD levels predicted to be likely to be therapeutic were associated with substantial reductions in several haematological indices of haemolysis [23]. These tests however are also surrogates, but more closely related to the basic pathology and hence can be regarded as more proximate to the disease than %MOD.…”
Section: The Properties Of Surrogates-their 'Dimensions'mentioning
confidence: 99%